Understanding verbal indirect communication in monolingual and bilingual children - Schulze, Cornelia; Quick, Antje Endesfelder; Gampe, Anja; Daum, Moritz M. (Cognitive Development, 2020)
Indirect communication occurs when a speaker does not explicitly say what s/he means but rather only hints at it and the recipient has to make inferences to uncover the speaker's actual intentions. Even though the majority of the world's population is bi- or multilingual, the comprehension of indirect communication has so far mainly been tested in monolingual children. This is surprising given some recent evidence indicating advantages for bilingual children in various communicative competences. In the present study, monolingual and bilingual 3-year-old children (n = 142) interacted with a speaker who communicated her preferences for certain actions indirectly (e.g., when offered cereals or toast for breakfast, saying, “I do have jam” which can be understood as a request for the toast). To uncover the speaker's intended object, children needed to draw a relevance inference in order to connect what was said with the question under discussion. The results showed that monolingual and bilingual children did not differ in their understanding of the speaker's indirectly communicated intentions and that the exposure to more than one language did not influence children's ability to draw relevance inferences. Thus, our study replicates earlier findings on monolingual children's comprehension of indirect communication, that is, the 3-year-old children in the present study performed above-chance level with relevance inferences. Moreover, our study adds to the current debate about bilingual children's communicative competences by showing that the existence and amount of further language input does not affect the interpretation of indirect meanings. Thus, seeking relevance seems to be a quite general disposition from early on in ontogeny.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Bilingualism; Cognitive abilities; Development; Indirect communication; Intention-reading; Relevance inference